Design optimization of backscatter X-ray security scanner based on pencil-beam scanning. (1st January 2023) - An, G.; Park, J.; Seo, H.
Abstract: At national borders and high-security facilities, security screening is conducted to block the entrance of illicit goods such as weapons, explosives, and drugs. In the Republic of Korea, the Korea Customs Service currently conducts transmission X-ray security screening using fixed energy. However, the detection efficiency of this system for drugs or explosives composed of organic substances is rather low. Alternatively, the backscatter X-ray detection system is sensitive to materials of low atomic number; therefore, it can play an essential, complementary role in security screening. In the present study, the design of a pencil-beam-based backscatter X-ray security scanner was optimized and, subsequently, its performance was evaluated under various conditions using the Monte Carlo (MC) simulation technique. As for the X-ray generator, we optimized the tube voltage and the geometry of the chopper wheel collimator. Detector parameters including length, distance between detectors, and thickness also were optimized for detection efficiency. Finally, the performance of the optimized system was evaluated for various object conditions and postal phantoms.